Nursing Care of Infant with Epilepsy: A Case Study - Cut Fella Attaqy; Nova Fajri; Nenty Septiana (Chakra Brahmanda Lentera Institute, 2023)
Background: Epilepsy is a number of symptoms of impaired brain function which are characterized by recurrent seizures due to excessive discharge of the brain's electrical charge and it is reversible. The impact caused by epilepsy is growth and development disorders, including impaired intelligence function, language comprehension and cognitive function disorder. Morover, there are very complex disorders on the brain which can cause behavioral and learning disorders, physical and mental disabilities, and death. This study aimed to find out the infant nursing care on A patient with epilepsy. Methods: This research uses a case study design. Data collection from assessment to evaluation in the in Arafah Room 1 of the Hospital in Banda Aceh on December 2022. Epileptic patients was observed or treated for 4 days. Data collection techniques ware carried out through interviews, observation, and documentation. Data analysis was carried out using narrative analysis. Results: Baby A with chief complaint of recurrent seizures. nursing diagnoses in the case of Baby A were ineffective breathing pattern, risk of ineffective tissue perfusion, risk of injury, lack of knowledge, and anxiety. The interventions provided are based on the Indonesian Nursing Intervention Standards which consist of observational, therapeutic and collaborative interventions. Conclusion: Nursing problems in Infant A after 4 days of treatment are show problem of ineffective breathing pattern and the the lack of knowledge about epilepsy was solved, the risk of ineffective cerebral tissue perfusion, the risk of injury, and anxiety were partially solved.